Memotivasi Anak Usia Dini Menabung Demi Masa Depan di Kelurahan Perdagangan I - Uli Wulan Dari; Tri Zahwanda; Fiya Oktavia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This community service activity aims to improve children's financial literacy and motivate them to save from an early age. This activity was carried out in Perdagangan I Village, Bandar District, Simalungun Regency on August 19-20, 2024 targeting children in grades 5 and 6 at Satrya Budi Perdagangan I Elementary School. The method used involved socialization and making piggy banks from used plastic bottles decorated according to the children's wishes, in order to increase their motivation to save. In addition, the community service team also conducted a Focus Group Discussion (FGD) to get feedback on the methods and materials provided. The results of the activity showed that the level of children's financial literacy was still low, where most children did not have the habit of saving and tended to spend their pocket money. After the activity, there was an increase in motivation to save and understanding of the importance of financial literacy, although there were still challenges in implementing the habit of saving consistently. This activity had a positive impact with the increase in enthusiasm of children and parents in understanding the importance of saving for the future. The activity is expected to contribute to increasing public awareness of the importance of financial literacy from an early age.